A comparative evaluation of microwave antenna designs performance on digital MR image in hyperthermia system. (2017) - Sethi, Minu; Nijhawan, Geeta
An efficient hyperthermia system is presented to evaluate and compare the performance of rectangular E-shape microwave antenna with two different circular shape antennas on digital magnetic resonance (MR) image of brain tumour that caters all the limitations. IE3D software is used to design microwave antennas for centre frequency of 2.45 GHz and a program is developed on MATLAB which shows how thermal imaging is done by applying the electromagnetic (EM) signal on the region of interest (ROI) in MR image of brain tumour. The system combines the data processing and analysis. It is simple and easy to use in order to obtain both quantitative values and images of temperature changes. Heating up to 45°C with minimal damage to surrounding healthy tissues is the prime focus of research. For real-time analysis, the antenna designs are fabricated and tested. The evaluated results illustrate the potential of designed antennas for hyperthermia treatment applicators.